2016
DOI: 10.1515/ijafr-2016-0015
|View full text |Cite
|
Sign up to set email alerts
|

A field-based comparison of ammonia emissions from six Irish soil types following urea fertiliser application

Abstract: Ammonia (NH3 ) emissions from a range of soil types have been found to differ under laboratory conditions. However, there is lack of studies comparing NH 3 emissions from different soil types under field conditions. The objective was to compare NH 3 emissions from six different soil types under similar environmental conditions in the field following urea fertiliser application. The study was conducted on a lysimeter unit and NH 3 emissions were measured, using wind tunnels, from six different soil types with v… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…Here we show that wide scale use of urea fertilisers would result in significantly less N 2 O than AN applications; however, past studies have shown that yield and quality of crops are higher when AN is applied, especially for grasslands ( Chambers and Dampney, 2009 , Cowan et al, 2020 ). Urea is also associated with much higher ammonia (NH 3 ) emissions than AN ( Burchill et al, 2016 , Forrestal et al, 2016 ), and so an element of pollution swapping is estimated to occur if urea fertilisers were used to replace AN at a national scale. Previous studies have indicated that urea treated with microbial inhibitors may result in slightly higher yields and lower NH 3 emissions than untreated urea ( Cantarella et al, 2018 , Misselbrook et al, 2014 , Silva et al, 2017 ), but this is still uncertain (some experiments show reduced yield ( Harty et al 2016 )) and AN (or CAN) remains the fertiliser favoured by farmers in the UK for yield and crop quality.…”
Section: Discussionmentioning
confidence: 99%
“…Here we show that wide scale use of urea fertilisers would result in significantly less N 2 O than AN applications; however, past studies have shown that yield and quality of crops are higher when AN is applied, especially for grasslands ( Chambers and Dampney, 2009 , Cowan et al, 2020 ). Urea is also associated with much higher ammonia (NH 3 ) emissions than AN ( Burchill et al, 2016 , Forrestal et al, 2016 ), and so an element of pollution swapping is estimated to occur if urea fertilisers were used to replace AN at a national scale. Previous studies have indicated that urea treated with microbial inhibitors may result in slightly higher yields and lower NH 3 emissions than untreated urea ( Cantarella et al, 2018 , Misselbrook et al, 2014 , Silva et al, 2017 ), but this is still uncertain (some experiments show reduced yield ( Harty et al 2016 )) and AN (or CAN) remains the fertiliser favoured by farmers in the UK for yield and crop quality.…”
Section: Discussionmentioning
confidence: 99%
“…These correlations from the incubation studies were much stronger than the correlation in the present study ( P = 0.100, R 2 = 0.337), suggesting that although clay content can accurately predict NH 3 volatilization under controlled conditions, the relation becomes more variable under field conditions, where wind speed, soil and air temperature, and soil water content are all allowed to fluctuate. Indeed, a previous field study found no effect of soil clay content on NH 3 volatilization losses after urea application (Burchill et al, 2016). However, the clay content of the soils in the Burchill et al (2016) study ranged from 11 to 28%, which may not be a sufficient range to see an effect.…”
Section: Discussionmentioning
confidence: 96%
“…Indeed, a previous field study found no effect of soil clay content on NH 3 volatilization losses after urea application (Burchill et al, 2016). However, the clay content of the soils in the Burchill et al (2016) study ranged from 11 to 28%, which may not be a sufficient range to see an effect. The current study used soils where clay content ranged from 5 to 57%, which was a sufficient range to detect the effect of clay content on NH 3 losses under field conditions.…”
Section: Discussionmentioning
confidence: 96%
“…The above observation suggests an over-estimation of EFs used in the Irish NH 3 inventory. There is therefore the need to generate additional datasets on NH 3 emissions from cattle buildings to validate the findings from Burchill et al (2017a). In the case of concrete farmyards or hard standings, mean EFs generated from the analysis of this review was 35% TAN.…”
Section: Cattle Buildings and Concrete Farmyardsmentioning
confidence: 94%
“…Table 3 summarises NH 3 EFs generated from cattle buildings and concrete yards used by cattle under Irish conditions. Emissions from cattle buildings can vary to a considerable extent due to variations in factors such as building design/ size, number of cattle and wind velocity/direction (Burchill et al, 2017a). Burchill et al (2017a) quantified NH 3 EFs from four cattle buildings which varied in size, floor type as well as the type and number of livestock housed.…”
Section: Cattle Buildings and Concrete Farmyardsmentioning
confidence: 99%